2021
DOI: 10.1021/acs.jpcc.1c08146
|View full text |Cite
|
Sign up to set email alerts
|

Impedance of Thermal Conduction from Nanoconfined Water in Carbon Nanotube Single-Digit Nanopores

Abstract: There has been recent interest in understanding the transport of nanoconfined fluids through single-digit nanopores (SDNs) or those smaller than 10 nm in diameters, where confinement alters the fluid structure and intermolecular potential. Thermal measurements on such systems are crucial to extracting phase boundaries and the thermodynamic properties of fluids under extreme confinement. In this work, we introduce a metrology approach based on micro-Raman spectroscopy of isolated, free-standing replicates of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 96 publications
0
11
0
Order By: Relevance
“…2c, water molecule forms HBs with both the water molecules in the cross-section and axial direction, generating a hexagonal tube-like HB network. Other studies 69,70 had also reported this hexagonal water structure in (9,9) CNT, which exhibited ice-like behaviour and very low diffusion capability. In OH-(9,9) CNT, the average q between water dipole with z axis is ca.…”
Section: Water Orientation and Hydrogen Bonds Formed Inside Cntsmentioning
confidence: 62%
“…2c, water molecule forms HBs with both the water molecules in the cross-section and axial direction, generating a hexagonal tube-like HB network. Other studies 69,70 had also reported this hexagonal water structure in (9,9) CNT, which exhibited ice-like behaviour and very low diffusion capability. In OH-(9,9) CNT, the average q between water dipole with z axis is ca.…”
Section: Water Orientation and Hydrogen Bonds Formed Inside Cntsmentioning
confidence: 62%
“…The ultrafast transport property in nanoconfined liquid offers a unique opportunity for heat and mass transfer, holding potential to address the bottleneck in the thermal management of high-power density electronic devices with local heat flux up to 10 3 W/cm 2 and concentrated heat sources. , However, the thermal properties of nanoconfined water are controversial because of opposite findings on the confinement effects on phonon activities and thermal conduction. Specifically, atomistic simulation has revealed that the nanoconfinement can reduce the thermal conductivity of water in a copper channel due to enhanced phonon scattering at the solid–liquid interface, indicated by the redshift of peaks in the vibrational spectrum . In contrast, the thermal conductivity of water confined in a subnanometer graphene channel is increased to twice the bulk value with suppressed phonon scattering .…”
mentioning
confidence: 99%
“…Enhanced flow can be predicted by corrections to Hagen–Poiseuille theory, linking transport results inside isolated carbon nanotubes with less precise but more readily available measurements of membranes and multipore systems. , Thermodynamically, phase boundaries of water inside isolated single-digit carbon nanotubes vary nonmonotonically with confining diameter in ways that cannot be explained by existing theories . Finally, recent advances in fabrication of isolated carbon nanotube systems by segmentation of ultralong carbon nanotubes into shorter segments , allow comparison between filled and empty segments of the same diameter and chirality carbon nanotube.…”
mentioning
confidence: 99%
“…24,25 Thermodynamically, phase boundaries of water inside isolated single-digit carbon nanotubes vary nonmonotonically with confining diameter in ways that cannot be explained by existing theories. 19 Finally, recent advances in fabrication of isolated carbon nanotube systems by segmentation of ultralong carbon nanotubes into shorter segments 26,27 allow comparison between filled and empty segments of the same diameter and chirality carbon nanotube. Herein, we observe closed, isolated carbon nanotubes that appear either empty, completely filled with liquid water, or partially water-filled.…”
mentioning
confidence: 99%
See 1 more Smart Citation